Incidence and factors associated with pericardial effusion after cardiac valve surgery - Martins, Eduardo Ferreira; Pereira Neto, Adriano Heemann; Danielli, Lucas; Nunes, Lisandra Almeida; do Amaral, Maria Vitória França; Kalil, Paulo; Wender, Orlando; Foppa, Murilo; Santos, Ângela Barreto Santiago (Clinical and Biomedical Research, 2017)
Introduction: Pericardial effusion (PE) is a postoperative complication of cardiac valve surgery, related to early hospital readmissions and death. We aimed to describe its incidence and to identify predictive factors of moderate-to-severe PE in a contemporary cohort. Methods: We retrospectively reviewed medical records of all consecutive patients submitted to cardiac valve surgery in a tertiary teaching hospital from January 2012 to July 2014, where echocardiography was routinely performed before patient discharge. Moderate-to-severe PE was defined as ≥ 10 mm of thickness, or signs of cardiac tamponade on echocardiography. Additional clinical and perioperative data were extracted from medical records using a standardized protocol. Results: Of 353 patients, 335 underwent a predischarge echocardiography. From these, 27 patients (8%; mean age: 62 years; standard deviation 12 years; 70% male) had moderate-to-severe PE. These patients had a higher prevalence of previous stroke (22% vs. 8%; p = 0.009) and oral anticoagulation (international normalized ratio > 2) prior to the surgery (11 vs. 2%; P = 0.002). In patients with moderate-to-severe PE, surgeries had longer ischemia (p < 0.001) and cardiopulmonary bypass (p < 0.001) times, and the prevalence of postoperative atrial fibrillation was higher (56% vs. 32%; p = 0.011) than in patients with absent or small PE. Hospital mortality was also higher (15% vs. 3%; p = 0.002) in patients with moderate-to-severe PE. Conclusions: Eight percent of patients submitted to cardiac valve surgery developed moderate-to-severe PE. Moreover, PE was associated with pre- and post-surgery conditions likely related to the coagulation state, though a cause-effect relationship could not be inferred. Noteworthy, this condition was associated with higher in-hospital morbidity and mortality. Keywords: Adult; pericardium; postoperative care